Benefits of Subliminal Feedback Loops in Human-Computer Interaction. (26th August 2010) - Ritter, Walter
Abstract : A lot of efforts have been directed to enriching human-computer interaction to make the user experience more pleasing or efficient. In this paper, we briefly present work in the fields of subliminal perception and affective computing, before we outline a new approach to add analog communication channels to the human-computer interaction experience. In this approach, in addition to symbolic predefined mappings of input to output, a subliminal feedback loop is used that provides feedback in evolutionary subliminal steps. In two studies involving concentration-intensive games, we investigated the impact of this approach. In a first study evolutionary feedback loops adjusted the user interface of a memory game whereas in the second study the lighting of the test room was adjusted dynamically. The results show that in settings with an evolutionary feedback loop test participants were able to reach significantly higher scores compared to the static counterparts. Finally, we discuss the impact that such subliminally working applications might have on the user's acceptance.